Cologne, oppidum des Ubiens : l’urbanisme augustéen - Alfred Schäfer (Gallia)
The Oppidum Ubiorum (the future Cologne) was set up on imperial initiative, on the land recently attributed to the transrhenane people of Ubii. From its birth, probably in the last decade BC, it had the appearance of a provincial capital. Its typically Roman urbanism and its cultural features, were characteristic of a population from the Italian peninsula, not native. The Roman army probably played an important part in the rise of this provincial centre, located in a fertile area, well-linked to the rest of Gaul by the major roads of the Augustan network. Thus, Cologne was a Roman town, not a native one, with an exceptional purpose and played a major part in the organization and economy of the province of Germany.